2004
DOI: 10.1128/jb.186.16.5376-5383.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis YhcR, a High-Molecular-Weight, Nonspecific Endonuclease with a Unique Domain Structure

Abstract: In a continuing effort to identify ribonucleases that may be involved in mRNA decay in Bacillus subtilis, fractionation of a protein extract from a triple-mutant strain that was missing three previously characterized 3-to-5 exoribonucleases (polynucleotide phosphorylase [PNPase], RNase R, and YhaM) was undertaken. These experiments revealed the presence of a high-molecular-weight nuclease encoded by the yhcR gene that was active in the presence of Ca 2؉ and Mn 2؉ . YhcR is a sugar-nonspecific nuclease that cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It is also possible that the protein substrates were missing features not yet identified that are required for enzyme activity. The genome of B. subtilis contains two putative sortase-encoding genes whose functions have not been characterized (46,47). As functional Cel8A protein was not displayed when SrtA was absent, these endogenous enzymes were presumably unable to anchor Cel8A to the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the protein substrates were missing features not yet identified that are required for enzyme activity. The genome of B. subtilis contains two putative sortase-encoding genes whose functions have not been characterized (46,47). As functional Cel8A protein was not displayed when SrtA was absent, these endogenous enzymes were presumably unable to anchor Cel8A to the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the ␤-lactamase reporter fused to CWAD YhcRMO2 was biologically active. (45) suggests that YhcR is a nuclease that may anchor to the cell wall covalently. In this study, B. subtilis yhcS and the sequence encoding the cell wall anchoring domain of YhcR were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that anchoring YfkN to the cell wall minimizes the proteolytic cleavage of the membrane-bound form of YfkN by B. subtilis proteases. Since both YhcR and YfkN can be detected in the culture medium (8,22,45), this observation poses an interesting question concerning the purpose of immobilizing these enzymes on the cell surface. Although there is no definite answer to this question, the presence of YhcR and YfkN in both the wall-bound forms and the proteolytic cleaved forms in the culture supernatant can possibly be considered a very elegant strategy employed by B. subtilis.…”
Section: Characterization Of Yhcr By Oussenko and Coworkersmentioning
confidence: 99%
See 1 more Smart Citation
“…RNase III and a sugar-nonspecific endoribonuclease have been identified in B.subtilis (16–18), but this organism has no homologues of the two essential E.coli endoribonucleases, RNase E ( rne ) and oligoribonuclease ( orn ). However, an activity similar to the former probably exists in this organism (19).…”
Section: Introductionmentioning
confidence: 99%